High‐Performance Electrostrictive Relaxors with Dispersive Endotaxial Nanoprecipitations. Issue 36 (7th August 2022) - Liu, Ye; Deng, Shiqing; Li, Jun; Huo, Chuanrui; Wang, Lu; Sun, Shengdong; Zhang, Yueyun; Wu, Jie; Liu, Hui; Qi, He; Chen, Jun
Abstract: Ultrahigh‐precision manufacturing and detection have highlighted the importance of investigating electrostrictive materials with a weak stimulated extrinsic electric field and a simultaneous large hysteresis‐free strain. In this study, a new type of electrostrictive relaxor ferroelectric is designed by constructing a complex inhomogeneous local structure to realize excellent electrostrictive properties. A remarkably large electrostrictive coefficient, M 33 (8 × 10 −16 m 2 V −2 ) is achieved. Through a combined atomic‐scale scanning transmission electron microscopy and advanced in situ high‐energy synchrotron X‐ray diffraction analysis, it is observed that such superior electrostrictive properties can be ascribed to a special domain structure that consists of endotaxial nanoprecipitations embedded in a polar matrix at the phase boundary of the rhombohedral/tetragonal/cubic phases. The matrix contributes to the high strain response under the weak extrinsic electric field because of the highly flexible polarization and randomly dispersed endotaxial nanoprecipitations with a nonpolar central region, which provide a strong restoring force that reduces the strain hysteresis. The approach developed in this study is widely applicable to numerous relaxor ferroelectrics, as well as other dielectrics, for further enhancing their electrical properties, such as electrostriction and energy‐storage capacity. Abstract : Via the construction of novel local heterostructures of polar nanoregions and endotaxial nanoprecipitations with a nonpolar core in relaxor ferroelectric ceramics, an unprecedentedly large hysteresis‐free strain is achieved under a low stimulated electric field, which is suitable for the application of ultrahigh precision actuator systems. The new strategy can open a new realm for the design of high‐performance ferroelectric relaxors.